Comparative study between the prophylactics Effects of aqueous extract of Black Currant (Vitis vinferia.L) and vitamin E on some biological parameters related with heart diseases in oxidative Stressed rats: Abdul-Katum, A. H. and Khudair, K.K. - H., Abdul-Katum A. (The Iraqi Journal of Veterinary Medicine, 2008)
This study was designed to investigate the prophylactic effect of aqueousextract of black currant concentrate on some biological markers related withheart disease in male rat treated H2O2. It also aimed at comparing theprophylactic effect of black currant concentrate to that of vit E.Forty adult male rats were divided randomly into equal groups (tenrat/group) & were treated as follows for 42 days. Rats in the first group (G І)were received normal water with oral intubation of sun flower oil 1ml /rat andconsider as control group. Animals of the second group (G Π) were received0.5% H2O2 in drinking water, while rats of the third group (G Ш) were received0.5% H2O2 in drinking water with oral intubation of vit E 400 I.U/Kg.B.Wdiluting in sun flower oil for each rat daily .While animals in the fourth group (GІV) were intubated daily 60mg/kg body weight of aqueous extract of blackcurrant concentrate plus 0.5% H2O2 in drinking water.Fasting blood samples were collected at 0, 21, and 42 days of experimentto study the following parameters:A - Platelet count (PC) and prothrombin time (PT).B- Serum concentration of total cholesterol TC, triacylglycerol TAG, Highdensity lipoprotein-cholesterol HDL-C, Low density lipoprotein-cholesterolLDL-C and Very low density lipoprotein- cholesterol VLDL-C of each groupwere measured. These parameters were regarded as biomarkers ofatherosclerosis and coronary heart disease (CHD). Furthermore section of heart& aorta were assessed for histopathogical studies.The result revealed that administration of 0.5% H2O2 in drinking water for sixweeks (42days) caused significant increase (p<0.05) in platelet count & in serumTC,TAG,LDL-C, and VLDL-C concentration with significant decrease(p<0.05)in prothrombin time and HDL-C concentration as compared to other groups, onother hand oral intubation of vitamin E or aqueous extract of black currantconcentrate in addition to H2O2 (groups Ш and ІV respectively) decreased theserum concentration of TC, TAG, LDL-C, VLDL-C, and platelet countIraqi Journal of Veterinary Medicine Vol. 32, No. 2, 2008228